Global value chain participation and inclusive growth in sub-Saharan Africa - Camara Kwasi Obeng; Peter Y. Mwinlaaru; Isaac Kwesi Ofori (African Governance and Development Institute (AGDI), 2021)
Global value chain (GVC) participation has been identified as one of the means by which developing countries can attain inclusive growth yet little attention has been paid to it in sub-Saharan Africa (SSA). Motivated by the dearth of studies on SSA, we investigate the effect of GVC participation on inclusive growth for 19 SSA countries for the period 1991 to 2017, using the system GMM estimator. The results show that GVC participation drives inclusive growth through employment creation. We find that though SSA's foreign value addition is less than its domestic value addition, the former's impact on inclusive growth is higher than that of the latter. We recommend that policymakers support downstream industries to acquire technologies while incentivizing and attracting upstream industries into their countries.
Keywords: F14; F15; F43; F6; O4; Q55; 330; Global Value Chain; Inclusive Growth; Domestic Value Added; Foreign Value Added; Sub-Saharan Africa